Editorial Board - Purba, Julwan Hendry (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2020)
This section consists of Cover Page, Editorial Board Page, Peer Reviewer Page, Table of Content Page and Preface Page